2022
DOI: 10.3390/jrfm15080366
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Take-Up of Agricultural Insurance and the Entry into the Mutual Fund: A Case Study of the Czech Republic

Abstract: The objective of the study was to identify the main factors influencing farmers’ willingness to take up agricultural insurance and participate in a mutual fund for non-insurable risks in the Czech Republic. Responses from 214 representative farms were processed using descriptive statistics, paired t-tests, binary logistic regression, and contingency analysis. The regression model showed the influences of agricultural area, distrust in insurance companies, the probability of losing more than 20% of production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Farmers with large farm holdings did not worry about the time to purchase their farm input and did not involve themselves in off-farm activities since they had a sufficient financial capacity. This finding is in line with the studies of Mesfin et al (2011), Ullah et al (2015) and Kislingerova and Spicka (2022), in which large-scale farmers have a high capacity to bear risk and less need for risk management tools. Dabkiene (2020) signified that agricultural production on small farms was not sufficient to support the families; therefore, they were involved in diversification activities.…”
Section: Diversification Strategy Determinantssupporting
confidence: 91%
See 3 more Smart Citations
“…Farmers with large farm holdings did not worry about the time to purchase their farm input and did not involve themselves in off-farm activities since they had a sufficient financial capacity. This finding is in line with the studies of Mesfin et al (2011), Ullah et al (2015) and Kislingerova and Spicka (2022), in which large-scale farmers have a high capacity to bear risk and less need for risk management tools. Dabkiene (2020) signified that agricultural production on small farms was not sufficient to support the families; therefore, they were involved in diversification activities.…”
Section: Diversification Strategy Determinantssupporting
confidence: 91%
“…This finding was in line with the study of Nahraeni (2012). Moreover, Kislingerova and Spicka (2022) found that large farm size provides a greater management capacity and greater economies of scale for the farmers and could lead them to apply different risk management practices.…”
Section: Human Risk Management Strategy Determinantsmentioning
confidence: 99%
See 2 more Smart Citations
“…where L β E f ron is the maximum likelihood function of parameter β using the Efron partial likelihood method, β is the parameters of the regression model to be estimated, s j is the sum of each p predictor variable of the individual experiencing the event at time t j , D t j is the set of individuals who get the event at time t j , d j is number of cases of co-occurrence at time t j , and R t j is the set of individuals who have the risk of failing at time j. From Equation (4), the ln partial likelihood function is obtained as Equation ( 5), as follows [35,36]:…”
Section: Proportional Hazardmentioning
confidence: 99%